Adolescent Boys' Use of Emo Music as Their Healing Lament - Anastasi, Aaron P. (Journal of religion and health, 2005)
Emo music is one avenue through which God can begin or continue a process of healing found through connectedness, sharing, and understanding. God can use songs of lament to bring awareness of pain. Emo music can also offer an environment for the suffering individual to begin to think about and develop vocabulary to describe their pain. In some cases, the music can serve as a prayer of faith for the adolescent, allowing him to connect with God.